Financial performance and ownership structure: A comparison study between community development banks, government banks and private bank in Indonesia - Agustin, Hamdi; Md Rus, Rohani; Taufil Mohd, Kamarun Nisham (Human Resource Management Academic Research Society (HRMARS), 2013)
A unique characteristic of Indonesian banking system is the existence of community development banks, which is owned by local governments.This study examines the performance of this type of banks compared to private and federal government banks. The sample of this study consists of 15 community development banks, 56 private banks, and 3 federal government banks from 1995 to 2006. Using the independent t-test appropriate methodology. The financial performance of banks is measured in terms of profitability, capital structure, banks risk, efficiency, size and deposits measures.Government banks are about 11 times larger than community development banks and private banks.Subsequently, they have the greatest amount of current assets, debt, deposit, financing, and operational costs.However, in term of profits, either operational or net, their amount is not statistically different from the other two types of banks. In fact, in term of net profit, only community development banks show positive amount. Net profit between community development banks and private banks is significantly different. Community development banks have better ROA than government or private banks but the different is only significant between community development banks and private banks.In term of ROE, government banks have the highest ROE but it is not statistically significantly different to community development banks.ROE of either community development banks or government banks is significantly higher than that of private banks.